Anti-nephrin autoantibodies in steroid-resistant nephrotic syndrome may inform treatment strategy - Hengel, Felicitas Eugenia; Dehde, Silke; Yilmaz, Alev; Bayazit, Aysun K.; Ozaltin, Fatih; Paripovic, Dusan; Emma, Francesco; Ronco, Pierre; Vivarelli, Marina; Hogan, Julien; Schaefer, Franz; Tomas, Nicola M.; et al. (Kidney international, 2025)
Introduction - Autoantibodies against the podocyte protein nephrin were recently identified in a pediatric cohort primarily comprising steroid-sensitive (SSNS) and steroid-dependent (SDNS) nephrotic syndrome (NS). However, their prevalence across all NS subtypes, particularly in steroid-resistant nephrotic syndrome (SRNS), and their relation to therapy response need to be determined to advance pathophysiological understanding and refine treatment strategies. - Methods - A multicenter cohort study measuring anti-nephrin autoantibodies in samples from children with SSNS, SDNS, nongenetic and genetic SRNS was conducted. - Results - Sixty-nine of 101 (68%) patients with SSNS, 19 of 67 (28%) patients with SDNS, 14 of 103 patients (14%) with non-genetic SRNS, and 1 of 62 patients (2%) with genetic SRNS were positive for anti-nephrin autoantibodies. The prevalence of anti-nephrin autoantibodies increased with presence of active disease in cases of SSNS and SDNS. Within the group of non-genetic SRNS patients with active disease, anti-nephrin positivity was found in 13 of 74 (18%) patients responding to intensified immunosuppression compared to none of 17 patients with multidrug-resistant SRNS. - Conclusions - The prevalence of anti-nephrin antibodies is substantially higher in children with steroid responsive NS than in those with SRNS, suggesting that anti-nephrin antibodies primarily drive SSNS/SDNS. In contrast, NS due to podocyte gene mutations is primarily genotype-caused. Anti-nephrin autoantibodies may serve as a positive prognostic marker in pediatric NS, indicating a favorable response to immunosuppressive therapy.